Bioethics: the basics - Campbell, Alastair V. (Milton Park, Abingdon, Oxon : Routledge, 2013)
"Bioethics : The Basics is an introduction to the foundational princ iples, theories and issues in the study of medical and biological ethic s. Readers are introduced to bioethics from the ground up before being invited to consider some of the most controversial but important questi ons facing us today. Topics addressed include: - The range of moral the ories underpinning bioethics - Arguments for the rights and wrongs of a bortion, euthanasia and animal research - Healthcare ethics including t he nature of the practitioner-patient relationship - Public policy ethi cs and the implications of global and public health Concise, readable a nd authoritative, this is the ideal primer for anyone interested in the study of bioethics"--
Includes bibliographical references (pages 178-183) and index.
Keywords: Medical ethics; Bioethics; Social medicine; Ethics, Medical